Izod impact energy study of re-forced polisher matrix compounds with curaous fibers aligned and epoxy matrix reinforced with piassava fibers - Ferreira,Ailton da Silva (2018)
ABSTRACT Polymer matrix composites have been applied in components such as helmets and shielding for which toughness is a major requirement. Natural fiber presents interfacial characteristics with polymeric matrices that favor a high impact energy absorption by the composite structure. The objective of this work was then to assess the Izod impact resistance of polymeric composites reinforced with different amounts, up to 30% in volume, of a promising high strength natural fiber from the Amazon region known as curaua. Among these, the piassava fiber extracted from a palm tree native of South America stands as one of the most rigid with a potential to be used as composite reinforcement. Therefore, the present work investigates the notch toughness behavior, by Izod impact tests, of epoxy composites reinforced with up to 40 % in volume of continuous and aligned piassava fibers.The results showed a remarkable increase in the notch toughness with the amount of incorporated curaua fibers. This can be attributed to a preferential debonding of the fiber/matrix interface, which contributes to an elevated absorbed energy. . It was found that the incorporation of piassava fibers results in significant increase in the impact energy of the composite. Scanning electron microscopy analysis showed that the nature of the piassava fiber interface with the epoxy matrix is the major responsible for the superior toughness of the composite.